If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + a = 27 Reorder the terms: a + k = 27 Solving a + k = 27 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1k' to each side of the equation. a + k + -1k = 27 + -1k Combine like terms: k + -1k = 0 a + 0 = 27 + -1k a = 27 + -1k Simplifying a = 27 + -1k
| (3x-4)(x-2)= | | b^3-q^3=0 | | -16+n=-10 | | 9x=52 | | 23-3x=5+6x | | 7x-11y=72 | | 6x-70=2 | | 4x-2y=9 | | 25b^2-60b+36=0 | | mp=np+k | | 19x-7y=83 | | 17=9-2y | | a^4-1=0 | | 6m+3=2 | | -1+x=-9 | | -0.4(a-15)=0.1(a-1.5) | | 10+4x-4-x=27 | | .8+x=.428 | | 2x^2-5x=14 | | -0.4(a-15)=0.1(a-15) | | -3=-3(2x-3) | | 3x^2+20x-33=0 | | 4s^3-9s=0 | | -5x-9= | | 7x+10y-1=0 | | 8(4x-3)=7(x-6)+7 | | 7u+6v-4(5u-4v)= | | 8(2x-3)=2(8x+7) | | -(5xy-11)+3(3xy+7)= | | 7+3x-6=7x+9-2x | | 7+3x-6=7x+9-2 | | 104p-45=-95 |